2017
DOI: 10.1371/journal.pntd.0005458
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Bothrops atrox envenomation: Efficacy of antivenom therapy and the combination of Bothrops antivenom with dexamethasone

Abstract: Bothrops atrox snakes are the leading cause of snake bites in Northern Brazil. The venom of this snake is not included in the antigen pool used to obtain the Bothrops antivenom. There are discrepancies in reports on the effectiveness of this antivenom to treat victims bitten by B. atrox snakes. However, these studies were performed using a pre-incubation of the venom with the antivenom and, thus, did not simulate a true case of envenomation treatment. In addition, the local lesions induced by Bothrops venoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…The identification of a potent dermonecrotic factor in B. atrox venom has a clinical implication explaining why some patients bitten by B. atrox present more severe local lesions. Moreover, dermonecrosis induced by B. atrox venom in mice is not neutralized by antivenom, except if the antivenom is administrated soon after venom injection [ 49 ]. Thus, our results are important since they indicate that dermonecrosis is a direct effect of toxins and Atroxlysin-Ia may contribute greatly to the patient’s local condition thus deserving special attention for its neutralization by antivenoms.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a potent dermonecrotic factor in B. atrox venom has a clinical implication explaining why some patients bitten by B. atrox present more severe local lesions. Moreover, dermonecrosis induced by B. atrox venom in mice is not neutralized by antivenom, except if the antivenom is administrated soon after venom injection [ 49 ]. Thus, our results are important since they indicate that dermonecrosis is a direct effect of toxins and Atroxlysin-Ia may contribute greatly to the patient’s local condition thus deserving special attention for its neutralization by antivenoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Santos-Barreto et al [ 29 ] experimentally studied the combination of antivenom and dexamethasone and concluded that the use of this glucocorticoid as an adjunct to the antivenom therapy could be useful to improve the treatment of local symptoms observed in Bothrops envenomation.…”
Section: Action Of Premedication Drugsmentioning
confidence: 99%
“…In fact, B. atrox exhibits a dynamic use of its habitat, being known as one of the most active hunters of the Bothrops genus [9,11,12]. B. atrox venom causes mainly local damage, such as edema, hemorrhage and necrosis, apart from systemic effects, including blood coagulation disorders [13,14]. In lethal cases, hemorrhage leads to cardiovascular shock and acute renal failure secondary to acute tubular necrosis and occasionally glomerulonephritis [7,15].…”
Section: Introductionmentioning
confidence: 99%